2009
DOI: 10.1292/jvms.001343
|View full text |Cite
|
Sign up to set email alerts
|

Growth Inhibition of Human Melanoma Cells by a Recombinant Arginine Deiminase Expressed in Escherichia coli

Abstract: ABSTRACT. We have cloned the arginine deiminase (ADI) gene from Mycoplasma hominis PG21 genomic DNA by polymerase chain reaction, and changed four TGA tryptophan codons (stop codon in E. coli) to TGG codons in the coding region by site-directed mutagenesis in order to express in E. coli. The recombinant ADI (rADI) was purified to apparent homogeneity by Ni-affinity chromatography after extraction from inclusion bodies followed by refolding. The rADI expressed in E. coli was estimated to be 50 kDa. Dimeric form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Here, PAL was shown to be toxic for breast cancer MCF7 and prostate cancer DU145 cells. Compared with other anticancer enzymes, PAL has the similar cytotoxic effect with l ‐asparaginases and novel anticancer enzymes such as arginine deiminase and onconase . For example, IC 50 of l ‐asparaginase from E .…”
Section: Discussionmentioning
confidence: 99%
“…Here, PAL was shown to be toxic for breast cancer MCF7 and prostate cancer DU145 cells. Compared with other anticancer enzymes, PAL has the similar cytotoxic effect with l ‐asparaginases and novel anticancer enzymes such as arginine deiminase and onconase . For example, IC 50 of l ‐asparaginase from E .…”
Section: Discussionmentioning
confidence: 99%
“…[30] reported that the addition of L-arginine in the refolding solution was able to clearly increase the enzymatic activity of denatured ADI proteins. However, our experiments showed that the presence of L-arginine had no effect on the in-vitro solubilization of rADI proteins in the inclusion body form.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, it had been observed that the improvement of the substrate L-arginine for correct refolding of denatured ADI proteins in the refolding solution [30]. However, L-arginine had no effect on the in vitro solubilization of rADI proteins in inclusion body forms.…”
Section: Discussionmentioning
confidence: 99%
“…The inhibitory effect of native or recombinant arginine deiminase on the proliferation of tumor cells makes this enzyme a candidate for antitumor treatment (45). The main effects of arginine deiminase on these cells are depletion of arginine (46), inhibition of the cell cycle, and induction of apoptosis (41).…”
Section: Discussionmentioning
confidence: 99%